Ethnic Conflicts in Croatia? - Roksandić, Drago (Array, 1997)
In the context of a fast deruralisation and urbanisation in the 20th century Croatia, both Croats and Serbs and their newly emerging elites found themselves somewhere between their rural past and urban aspirations regarding cultural patterns, moral values, and understanding of civil rules and institutions. The heritage of "socialist self-management" - deeply divided between the totalitarian nature of the "dictatorship of the proletariat" and the coninuous failing attempts to establish "socialism with the human face" - made all those problems of interethnic relations more complicated due to the instrumental use of the "national question" by Communist structures of power, burdening even more Croato-Serbian/Serbo-Croatian relations ...